Anti-tubercular and probiotic properties of coagulase-negative staphylococci isolated from Koozh, a traditional fermented food of South India. (January 2018) - Khusro, Ameer; Aarti, Chirom; Dusthackeer, Azger; Agastian, Paul
Abstract : In the last few years, the demand for the tremendous therapeutic applications of indigenous probiotic bacteria from diversified fermented food products has surged. In view of this, the present study was documented to evaluate the anti-tubercular and probiotic properties of coagulase-negative staphylococci (CNS) indigenous to Koozh, a traditional fermented food product of South India. A total of 18 isolates were purified from Koozh, and tested for anti-tubercular activity against Mycobacterium tuberculosis H37Rv using luciferase reporter phage (LRP) assay. Among them, six isolates revealed higher percentage (>90%) of relative light unit (RLU) reduction. These six isolates were further evaluated for their in vitro probiotic attributes using standard protocols. All six staphylococci strains disclosed good probiotic properties. Moreover, Staphylococcus hominis strain MANF2 showed high cell survival percentage (92.2%) at pH 2.0 as well as towards simulated gastric juice (88.51%). Furthermore, strain MANF2 was found to be resistant to bile salt after 24 h of incubation with maximal viability of 5.71 ± 0.02 log cfu/mL, and depicted the deconjugation of bile salt as well. All the isolates exhibited strong auto-aggregation capacity (44.4 ± 1.2–68.1 ± 1.5%), and hydrophobicity against toluene (55.0 ± 1.2–72.0 ± 1.1%). Additionally, strain MANF2 was observed to be highly resistant to phenol (6.27 ± 0.01 log cfu/mL) and lysozyme (81.1 ± 1.6% viability). Most importantly, all six isolates depicted good hypocholesterolemic effect, slight β-galactosidase activity, and moderate proteolytic property. The strains were sensitive to all the tested conventional antibiotics, except Nalidixic acid. In addition to this, all staphylococci strains demonstrated significant DPPH (2, 2-Diphenyl-1-picrylhydrazyl) scavenging, hydrogen peroxide tolerance, and hydroxyl radical scavenging activity in a dose dependent manner, thereby exhibiting the potent antioxidative properties of isolates. The negative results obtained from haemolytic, DNase, and gelatinase tests revealed the non-pathogenicity and safety aspect of these strains. In a nutshell, the present investigation divulges the persuasive anti-tubercular and probiotic properties of staphylococci, particularly strain MANF2, and recommended the further exploitation of Koozh associated CNS in pharmaceutics. Highlights: Coagulase negative staphylococci (CNS) showed remarkable anti-tubercular property. Staphylococci strains disclosed good probiotic properties and survived upto pH 2. All six staphylococci demonstrated significant antioxidative characteristics. Safety assessment and antibiotic test revealed non-pathogenicity of CNS. Utilization of S. hominis strain MANF2 in pharmaceutics has been suggested.